Reversion towards benzimidazole susceptibility in Haemonchus contortus by resistance management strategies - C P SWARNKAR; D SINGH; F A KHAN; S R SHARMA (Indian Journal of Animal Sciences, 2021)
A study was aimed to observe the impact of withdrawal of anthelmintic type and increase in refugia through community dilution on reversion towards benzimidazole (BZ) susceptibility in Haemonchus contortus at an organized sheep farm in semi-arid Rajasthan. In sheep flocks of ICAR-Central Sheep and Wool Research Institute, Avikanagar reduced efficacy (80%) on faecal egg count reduction test (FECRT) with ED50 of 0.239 μg thiabendazole (TBZ)/ml on egg hatch assay (EHA) indicative of emergence of H. contortus resistant to BZ was observed in the year 1995. Following discontinuation of BZ for deworming at farm since 1996, the efficacy varied between 0-44% in the year 2000 with predominance of BZ-resistant alleles (>90%) between the year 2005 to 2010. efficacy was still low (26% on FECRT, ED50 of 0.196 Î¼g TBZ/ml on EHA) even after 15 yr post withdrawal (in 2010). Later on, the concept of community dilution and refugia were implemented for worm management. With these strategies, during 2018-20 (22 yr post withdrawal) a significant improvement (86-93%) in efficacy of BZ was noticed against H. contortus. Simultaneously, the ED50 values ranged from 0.011 to 0.119 with an average of 0.075±0.008 μg TBZ/ml on EHA with prevalence of BZ susceptible alleles up to 48% on allele specific PCR assay. The study indicates the possibility of reversion to BZ susceptibility in H. contortus population in farm area with community dilution and refugia based worm management strategies.